Inequalities in HIV disease management and progression in migrants from Latin America and sub‐Saharan Africa living in Spain. Issue 5 (21st November 2012) - Monge, S; Alejos, B; Dronda, F; Del Romero, J; Iribarren, JA; Pulido, F; Rubio, R; Miró, JM; Gutierrez, F; Del Amo, J; ,
<x xml:space="preserve">Abstract</x> Objectives The objective of the study was to analyse key HIV‐related outcomes in migrants originating from Latin America and the Spanish‐speaking Caribbean (LAC) or sub‐Saharan Africa (SSA) living in Spain compared with native Spaniards (NSP). Methods The Cohort of the Spanish AIDS Research Network (CoRIS) is an open, prospective, multicentre cohort of antiretroviral‐naïve patients representing 13 of the 17 Spanish regions. The study period was 2004–2010. Multivariate logistic or Fine and Gray regression models were fitted as appropriate to estimate the adjusted effect of region of origin on the different outcomes. Results Of the 6811 subjects in CoRIS, 6278 were NSP (74.2%), LAC (19.4%) or SSA (6.4%). For these patients, the follow‐up time was 15870 person‐years. Compared with NSP, SSA and LAC under 35 years of age had a higher risk of delayed diagnosis [odds ratio (OR) 2.0 (95% confidence interval (CI) 1.5–2.8) and OR 1.7 (95% CI 1.4–2.1), respectively], as did LAC aged 35–50 years [OR 1.3 (95% CI 1.0–1.6)]. There were no major differences in time to antiretroviral therapy (ART) requirement or initiation. SSA exhibited a poorer immunological and virological response [OR 0.8 (95% CI 0.7–1.0) and OR 0.7 (95% CI 0.6–0.9), respectively], while no difference was found for LAC. SSA and LAC showed an increased risk of AIDS for ages between 35 and 50 years [OR 2.0 (95% CI 1.1–3.7) and OR 1.6 (95% CI 1.1–2.4), respectively], which was attributable to a higher incidence of tuberculosis. However, no statistically significant differences were observed in mortality. Conclusions Migrants experience a disproportionate diagnostic delay, but no meaningful inequalities were identified regarding initiation of treatment after diagnosis. A poorer virological and immunological response was observed in SSA. Migrants had an increased risk of AIDS, which was mainly attributable to tuberculosis.